MUROJA’AH TERPADU DALAM KEGIATAN APEL PAGI: SEBUAH PENDEKATAN HOLISTIK UNTUK PENGEMBANGAN SPIRITUAL DAN KOGNITIF SISWA MI MIFTAHUL ULUM UJUNGWATU - Mushthofa, Aman; Aidi, Muhammad Ulil; Sukarman, S; Rozaq, Abdul (MAMBA'UL 'ULUM, 2025)
Muroja’ah is an activity of repeating memorization that is effective in enhancing students' memorization abilities, particularly in spiritual aspects such as memorizing Juz Amma and prayer recitations. This study aims to analyze the implementation of integrated muroja’ah activities during the morning assembly as a holistic approach that not only strengthens students' spiritual dimension but also their cognitive dimension through basic math exercises. The research was conducted at MI Miftahul Ulum Ujungwatu using a descriptive qualitative approach. The results of the study show that the integration of muroja’ah in the morning assembly enhances student engagement, strengthens memorization, and improves basic numeracy skills. This research provides insights for schools to utilize the morning assembly time as a moment for the comprehensive development of students' potential.